Prenatal bisphenol A and/or diethylhexyl phthalate exposure followed by adult estradiol treatment affects behavior and brain monoamines in female rat offspring - Kaimal, Amrita; Hooversmith, Jessica M.; Al Mansi, Maryam H.; Cherry, Ariana D.; Garrity, Jillian T.; Holmes, Philip V.; MohanKumar, Puliyur S.; MohanKumar, Sheba M. J. (Frontiers in Endocrinology, 2025)
Women are at increased risk for mood disorders, which may be partly attributed to exposure to endocrine-disrupting chemicals (EDCs) during sensitive periods such as pregnancy. Exposure during these times can impact brain development in the offspring, potentially leading to mood disorders in later life. Additionally, fluctuating levels of endogenous estrogens, as seen during pregnancy, or the use of oral contraceptives, can further elevate this risk. This study examines the cumulative effects of prenatal EDC exposure combined with chronic low-dose 17β-estradiol (E2) treatment in adulthood on neurobehavioral outcomes. Pregnant Sprague-Dawley rats were orally dosed with vehicle, bisphenol A (BPA) (5 µg/kg body weight (BW)/day), low-dose (LD) diethylhexyl phthalate (DEHP) (5 µg/kg BW/day), high-dose (HD) DEHP (7.5 mg/kg BW/day), or a combination of the two (BPA+DEHP) from gestational days 6-21. At 3 months of age, female offspring were implanted with slow-release E2 pellets or were sham-implanted. Following a 90-day treatment period, behavioral testing was conducted, and serum hormones and brain monoamine levels were analyzed. Chronic E2 treatment in controls increased anxiety and reduced active coping behaviors. In DEHP- and BPA+DEHP-exposed offspring, E2 treatment reversed some of these effects. Dose-dependent alterations in circulating hormone levels and brain monoamines were observed. Dysregulation of the stress axis was particularly notable with the higher dose of DEHP. Overall, prenatal EDC exposure altered behavior, hormones, and brain monoamines, with adult E2 treatment further exacerbating some of these effects in female offspring.